The development of fire prevention basic learning application - Mohd Razali, Nur Syamimi; Rosetadman Sidek, Nur Atiqah; Mohd Rosli, Nur Fatin Farhanah (Universiti Teknologi Malaysia, 2020)
Fire prevention skills are necessary for preventing a person from being caught in uncontrollable spread of fire. Therefore, every person has to equip him/herself with the basic knowledge of handling fire at the early stage. The aim of this study is to develop an application on basic fire prevention. The study seeks to achieve the following two objectives: (i) to develop and design a basic fire prevention application with embedded multimedia elements and (ii) to test the functionality of the application in terms of content, interface, and interaction aspect. The rapid prototyping model (analysis of needs, objectives, designs, testing and implementation) was selected as a development model and the behaviourism learning theory was applied. Adobe Flash Professional CS6 was chosen as the development platform. The application consists of three modules: “You Need to Know,” “Mind Test,” and “Guide.” To test the functionality of the application, the developer collected data from three experts from the Faculty of Technical and Vocational Education and Malaysia Civil Defence Force Officer, Batu Pahat. The three experts were selected through targeted sampling. The result concluded that the application was smooth in terms of functionality thus is suitable for new learners to learn about basic fire prevention.